Efeito do treino de força de preensão e destreza manual em crianças com síndrome de down de 5 a 10 anos - Oliveira, Cristina Camargo de (Universidade Federal de São Carlos, 2018)
Down syndrome is a genetic disorder that causes physical and cognitive changes. These characteristics may directly or indirectly affect the quality of life of individuals, such as slowness in acquiring new skills, minor hand size, short stature, among others. At the school stage there is a requirement for specialized movements regarding hand skills and all controls involved with that member. This research was subdivided into three studies. The first study verified in the scientific literature research related to the evaluation of the manual dexterity of children and adolescents with Down syndrome. A search of literature in the last 10 years in the databases LILACS, MEDLINE, SciELO, PubMed, Scopus with the descriptors: manual dexterity, fine motor skills, fine motor coordination, Down syndrome, evaluation and intervention. We found eight studies focused on the subject, with only two of them having intervention proposals with this population. The second study aimed to compare the manual dexterity and maximum grip strength of children with Down syndrome with typical children, from 6 to 10 years and 11 months. It was a study composed of two groups, matched according to age and sex, being the group of children with Down syndrome (10) and the group of typical children (10). The evaluations used were MABC-2, Box and Blocks test and dynamometer, and anthropometric data were also verified, such as weight, height and size of the dominant hand. Our results demonstrated that children with Down syndrome have a significantly lower performance than typical children for all abilities evaluated, as well as have a smaller hand size and smaller stature. We highlight in our results the size of the lower hand presented by the population with Down syndrome, which may be one of the justifications for low performance in the skills evaluated. The third study aimed to verify the effect of specific training for manual dexterity (fine and coarse), maximum grip strength and stereognosis in children with Down syndrome and typical children aged 5 to 10 years. In order to evaluate the children we used the same procedures of the second study, plus the evaluation of Stereognosis described by Teixeira. For this study we had a sample of 42 children, divided and matched into three groups: experimental group (14), composed of children with Down syndrome; motor control group (14), and social control group (14), both composed of typical and healthy children. Our results showed that after a period of nine specific training sessions, children with Down syndrome presented a better performance for the skills of thick manual dexterity, strength and stereognosis. For the skill of fine manual dexterity we could not present a significant improvement in the post-workout, however, we emphasize that the motor control group, which received the same training as the experimental group, showed a significant improvement, unlike the social control group, which despite of having performed better in post-training, was not significant. We therefore emphasize the importance of specific training to improve the performance of children with Down syndrome. It is suggested that future studies have a greater number of intervention sessions in order to offer more expressive gains for the manual skills, especially for fine manual dexterity.
Effect of training of maximum grip strength and manual dexterity in Down syndrome children from five to ten years
Keywords: Síndrome de Down; Força de mão; Destreza manual; Down syndrome; Maximum grips strength; Manual dexterity; Stereognosis; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL